Deciphering the Complex Signaling Systems That Regulate Intestinal Epithelial Cell Death Processes and Shedding - Patterson, Angela M.; Watson, Alastair J. M. (Frontiers in Immunology, 2017)
Intestinal epithelial cells play a fundamental role in maintaining homeostasis. Shedding of intestinal cells in a controlled manner is critical to maintenance of barrier function. Barrier function is maintained during this shedding process by a redistribution of tight junctional proteins to facilitate closure of the gap left by the shedding cell. However, despite the obvious importance of epithelial cell shedding to gut health a central question is how the extrusion of epithelial cells is achieved, enabling barrier integrity to be maintained in the healthy gut and restored during inflammation remains largely unanswered. Recent studies have provided evidence that excessive epithelial cell shedding and loss of epithelial barrier integrity is triggered by exposure to lipopolysaccharide (LPS) or tumour necrosis factor (TNF). Subsequent studies have provided evidence of the involvement of specific cellular components and signalling mechanisms as well as the functionality of microbiota that can be either detrimental or beneficial for intestinal barrier integrity. This review, will focus on the evidence and decipher how the signalling systems through which the mucosal immune system and microbiota can regulate epithelial cell shedding and how these mechanisms interact to preserve the viability of the epithelium.